Przejawy i następstwa naruszania interesów konsumenta w obrocie towarowym - Piasna, Barbara (Wydział Prawa i Administracji UAM, 1973)
The writer of the article takes for granted that both the state interest and the individual consumer's interest should be safeguarded in the socialistic economy. In practice, however, the consumer's interests are directly or indirectly interfered with. In the broad sense his interests may be affected when there is a disproportion between demand and supply of goods and services, a hidden and unfounded rise of prices, inadequate development or location of retail units, etc. The consumer's interest can be also affected when he is shopping if the quality of the goods is not reflected in their price, if the consumer gets a smaller quantity of goods than he has required and paid for, if the price charged for the goods is higher than the list price, if low-grade goods are sold at te price of higher - -grade goods or if the outstanding amount of money for the separate items and the whole transaction are miscalculated. All activities of that type interfere directly with the consumer's interest. The consumer's interests are indirectly affected in the sphere of the processing industry and merchandise turnover when a surplus of raw materials and goods is obtained on purpose and sold on somebody's own account, when goods of unknown origin are introduced to the socialized trade turnover, when abuses take place at non-market sales, when lower-grade goods are produced because fewer raw materials have been used in manufacture than specified in the material consumption standards and technological recipes. All the cases of direct and indirect interference with the consumer's interests cause deviation from the planned directions of economic development, they depart from the principles of socialistic distribution of national income and hinder the bettering of the living standard of the community at large. Therefore it is necessary to punish severely the persons who commit crimes and to improve means of protecting the state interests and the individual consumer's interests.
Cases of Interference with the Consumer's Interest in Merchandise Turnover and Consequences of the Interference